PET/CT-aided biopsy of lung lesions enhances diagnostic efficacy, especially for lesions >3cm - Liu, Wangzheng; Ji, Bin; Bai, Lin; Gao, Shi (Frontiers in Oncology, 2024)
The purpose of this study was to compare the diagnostic efficacy of PET/CT-aided CT-guided and routine CT-guided transthoracic needle biopsy for lung lesions. A total of 458 patients with suspicious lung lesions were referred for CT-guided biopsy, with 227 patients assigned to the PET/CT group and 231 patients assigned to the CT group.The clinical characteristics and diagnostic yield were compared between the two groups.Furthermore, conducting subgroup analysis to evaluate the differences of diagnostic success or failure between the two groups. The sensitivity and diagnostic accuracy rate differed significantly (P = 0.035, P = 0.048). In the PET/CT group, the values were 95.7% and 96.3%, respectively, while in the CT group, they were 90.1% and 91.9%.When considering non-diagnostic cases, the overall diagnostic success rate increased markedly in PET/CT group (93.0% vs. 83.1%, P = 0.001). In our subgroup analysis, the PET/CT group demonstrated superiority in detecting lesions larger than 3 cm (OR, 4.81; 95CI%, 2.03 -11.36), while showing a moderate effect in lesions smaller than 3 cm (OR, 1.09; 95CI%, 0.42 -2.81). Significant effect modification was observed in large lesions in the PET/CT group (P for interaction = 0.023). In conclusion, 18 F-FDG-PET/CT enhances the diagnostic efficacy of CT-guided transthoracic needle biopsy for lung lesions, and the incremental value can be modified by lesion size, particularly when the diameter is larger than 3 cm.